Evolving Security Threats and Identity in the United Arab Emirates - Reuß, Anna. author. aut Link
XVI, 285 p. 1 illus.
Keywords: This book examines and conceptualises the determinants of threat perceptions in the United Arab Emirates (UAE) and contributes to a better understanding of how a nation’s self-conception shapes its perceptions of (in)security and emphasises the relevance of these dynamics for policymaking. It combines the societal approach of the English School of IR with securitization theory to offer a novel framework for analyzing threat perceptions. This book is relevant to students of Middle Eastern studies, gulf studies, international relations, and scholars who are interested in theoretical perspectives. Dr Anna Reuß has been a research associate at the Institute of Political Science, University of the Bundeswehr Munich (Germany) since 2021. She completed her doctorate with the highest distinction (summa cum laude) in 2024. Her Ph.D. project addresses threat perceptions in the Arab Gulf states. She received a research grant from the German Academic Exchange Service (DAAD) to carry out substantial fieldwork in the UAE and was a visiting scholar at the Department of International and Middle Eastern Studies at the American University in Dubai, UAE. She was a Visiting Fellow at the King Faisal Center for Research and Islamic Studies in Riyadh, Saudi Arabia.